Experimental study of flow and entrainment characteristics of an ejector for a petrochemical flare system. (23rd June 2022) - Ma, Jiamin; Zhang, Jinting; Zhang, Jiedong; Liu, Meili; Kong, Changyan
Flare systems can promote rapid and efficient combustion, using a pre-mixing device with nozzles and mixers, but there is a research gap in exploring gas flow characteristics. This study designs an ejector to improve petrochemical flare system performance, based on analyses of gas flow and entrainment characteristics. A hot wire anemometer is used to measure the gas flow behaviour in the ejector mixer. The results show that an increase of the number of nozzle orifices is conducive to premixing, and the distance between nozzle outlet and mixer inlet has limited influence on entrainment. The frequency spectrum shows the mixer is filled with high oscillatory random turbulence, which causes a high degree of noise. The results improve our understanding of the internal flow characteristics of an ejector which can be used to optimise ejector design and reduce noise. [Received: March 9, 2021; Accepted: October 29, 2021]